2007
DOI: 10.1101/gad.1545107
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy suppresses tumor progression by limiting chromosomal instability

Abstract: Autophagy is a bulk degradation process that promotes survival under metabolic stress, but it can also be a means of cell death if executed to completion. Monoallelic loss of the essential autophagy gene beclin1 causes susceptibility to metabolic stress, but also promotes tumorigenesis. This raises the paradox that the loss of a survival pathway enhances tumor growth, where the exact mechanism is not known. Here, we show that compromised autophagy promoted chromosome instability. Failure to sustain metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
785
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 867 publications
(830 citation statements)
references
References 47 publications
26
785
2
5
Order By: Relevance
“…The activation of autophagy in early tumour formation limits genomic instability by maintaining the metabolism of the cell, thereby reducing DNA damage and gene amplification, and thereby, tumourigenesis 127 . Autophagy has also been shown to trigger non-apoptotic cell death in tumours and hence, prevent malignancy 128,129 .…”
Section: Autophagy In Cancermentioning
confidence: 99%
“…The activation of autophagy in early tumour formation limits genomic instability by maintaining the metabolism of the cell, thereby reducing DNA damage and gene amplification, and thereby, tumourigenesis 127 . Autophagy has also been shown to trigger non-apoptotic cell death in tumours and hence, prevent malignancy 128,129 .…”
Section: Autophagy In Cancermentioning
confidence: 99%
“…Autophagy is ubiquitous in eukaryotic cells and important in development and in diverse pathophysiological conditions (5)-for example providing protection against neurodegeneration (6,7), infections (8,9) and tumor development (10)(11)(12)(13). Cells that are deficient in autophagy also demonstrate enhanced chromosomal instability (14,15), which may be related to the tumorigenesis associated with autophagy deficiency.…”
mentioning
confidence: 99%
“…Autophagy is potentially tumour suppressive at the initial stages of cancer development by preventing the toxic buildup of misfolded proteins and damaged organelles, which if persist, can increase oxidative stress, promote genomic instability and predispose cells to malignant transformation. Certainly, Mathew et al (2007Mathew et al ( , 2009) reported autophagy deficiency to induce an aberrant accumulation of the autophagy adaptor protein p62, increased ROS levels, abnormal gene amplification, DNA damage and aneuploidy. Cells lacking atg5 and overexpressing p62 exhibited a significantly higher tumourigenic potential compared with atg5-deficient cells overexpressing the control vector in xenograft studies (Mathew et al, 2009).…”
Section: Autophagymentioning
confidence: 99%